Development of a system to measure radius of curvature and speed of hammer head during turns in hammer throw - Murofushi, K.; Sakurai, S.; Umegaki, K.; Kobayashi, K. (International Journal of Sport & Health Science, 2005)
The aim of this study was to compare the radius of curvature and the estimated head speed as measured by sensors attached to a hammer with those calculated by video image analysis. The participant was the Japanese record holder(83m47). He threw a hammer with sensors which measured the force exerted along the length of the hammer cable using a tension meter made of a metal plate to which strain gauges were affixed, and the angular velocity perpendicular to the hammer cable using two IC accelerometers whose axes were aligned together with the hammer cable. The radius and speed obtained using the sensors were similar to those obtained from video analysis in values, but were slightly out of phase. This is because measuring the angular velocity by sensors eliminates translational motion and only produces results for rotational motion. The length of time required to obtain these results was shortened by the use of a hammer with sensors. Therefore, the system using sensors attached to a hammer will enable athletes and coaches to interpret the data about each throw while it is still fresh in their minds.